Treatment of eosinophilic annular erythema with upadacitinib - Wanyan Xiang; Siqi Zhang; Qiuju Li; Wenjun Zheng (Journal of Dermatological Treatment)
Introduction Eosinophilic ring erythema (EAE) is a rare eosinophilic dermatosis characterized by ring-shaped or arc-shaped papules and plaques, with eosinophilic infiltration throughout the dermis. Due to the rarity of EAE, established treatment guidelines are currently lacking.Case report In this report, we present a case of a middle-aged male patient with EAE who exhibited a poor response to systemic immunosuppressants but responded favorably to upadacitinib.Conclusion This case highlights the potential utility of upadacitinib in managing EAE, particularly in patients unresponsive to conventional therapies.